Fire Detection System - Raghavendra Singh (International Journal of Advanced Robotics and Automation Technology, 2024)
Fire detection systems are engineered to identify the presence of fire or smoke and notify individuals of possible hazards. These systems employ a range of sensors, such as smoke detectors, heat detectors, flame detectors, and advanced algorithms, to recognize indications of fire inception or spread. When a fire is detected, alarms are activated, facilitating swift responses to minimize dangers and forestall fire incidents.
Keywords: Fire detection; Protection; hazards; mitigation; sensors